Boost converter for low voltage energy harvesting applications: basic component selection - Che Mustapha, Nurul Arfah; Alam, A. H. M. Zahirul; Khan, Sheroz; Azman, Amelia Wong (IEEE, 2013)
Regulating energy from tiny sources such from ambient vibration to supply a continuous energy to power an electronics device is a beneficial and challenging work to do. Having very small energy usually less than 1 V, needs a boost circuit to power up the device. This paper shows that the passive components of a conventional boost converter play an important role to boost very small voltage. This paper also presents that switching frequency effects to boost voltage. Transient analyses have been performed using PSpice simulation tool to check the circuit response to various parameter changes. The proposed circuit with components L=160 µH, RL=10 kΩ and switching frequency fS=1 kHz with duty cycle D=0.5 results optimum performance of the circuit. This voltage converter is suitable for vibration energy harvesting having low frequency applications in kHz range. The application of this converter is expected to be in automotive, healthcare and industrial field.